STUDY OF CHARACTERISTICS, QUALITY, DEPOSTIONAL ENVIRONMENT, AND ESTIMATION OF COAL RESOURCES ON PIT X, EAST KUTAI REGENCY, EAST KALIMANTAN PROVINCE - Armando Rehbayak, Hose
Pit X is located in East Kutai Regency, East Kalimantan Province with an area of 7,54 km2. The research area is part of the mining business permit area owned by PT Ganda Alam Makmur. This study aims to determine the characteristics, quality, depositional environment, and estimation of coal resources in the research area. The primary data used in the study were in the form of outcrop data and maceral composition. Drill and quality data are also used in the form of secondary data. The research area is part of the Kutai Basin. Based on rock outcrop data and log correlation, the study area was divided into three unofficial rock units sorted old to young, namely Sandstone-Claystone Unit with C2, C, and C1 coal seams in lower delta plain depositional environment, Claystone Unit with coal seams B, A2, A1, A, and Conglomerate Unit in lower delta plain depositional environment. Based on the similarity of lithological features and literature studies, these three units are equated with the Middle Miocene-aged Maluwi Formation. The results of the analysis of the maceral composition showed that coal in the study area was deposited in the limnic hydrological regime in the limited influx, clastic marsh. Based on coal quality analysis, it shows coal ratings in the research area Subbituminous B – High Volatile B Bituminous Coal with an average calorific value of 3492,34 kcal/kg a.r. Calculation of coal resources based on modeling using Minescape 5.7 software. The estimated resources in the study area starting from the inferred, indicated, and measured categories are 7.489.518 tons, 27.036.756 tons, and 55,414.948 tons with a total resource of 89.941.223 tons.